Digital transformation in agricultural circulation: enhancing rural modernization and sustainability through technological innovation - Wang, Hengli; Zhang, Lili; An, Zhongyin (Frontiers in Sustainable Food Systems, 2025)
IntroductionAs digital transformation accelerates globally, the digitalization of agricultural product circulation (DAPC) is becoming a key driver of rural revitalization and sustainable agricultural development.MethodsThis study introduces a digital agriculture product circulation index (DAPCI) to assess the level of digitalization in agricultural product circulation and the influence of digitalization on rural modernization in China. Additionally, this study develops a rural agricultural modernization development index (RAMDI) to measure the extent of modernization across 30 provinces (from 2012–2023). The entropy weight method and a spatial error model are applied to capture both direct and indirect effects.ResultsThe findings reveal that digitalization significantly enhances rural agricultural modernization (RAM), particularly in technologically advanced regions, with strong spatial spillover effects benefiting neighboring areas. The results further reveal that the digitalization of agricultural circulation positively correlates with improved rural economic development; green innovation and industrial structure optimization emerge as key mechanisms for driving both environmental sustainability and economic growth.DiscussionThis research contributes to understanding how digital tools can reshape agricultural practices, making those practices more resilient, efficient, and environmentally friendly. By demonstrating the impact of digitalization on rural agricultural sustainability, this study highlights the importance of integrated technological innovations and management strategies for advancing sustainable agricultural development and climate resilience in rural economies.